Power and Priorities: The Growing Pains of Global Health; Comment on "Knowledge, Moral Claims and the Exercise of Power in Global Health" - Karen Ann Grépin (Kerman University of Medical Sciences, 2015)
Shiffman has argued that some actors have a great deal of power in global health, and that more reflection is needed on whether such forms of power are legitimate. Global health is a new and evolving field that builds upon the historical fields of public and international health, but is more multi-disciplinary and inter-disciplinary in nature. This article argues that the distribution of power in some global health institutions may be limiting the contributions of all researchers in the field